(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to study the relationship between the role of audit committees and the financial performance of companies. Especially the insurance companies operating in the Damascus Stock Exchange, and for that, the researcher collected data on the independent variable represented in the formation of the audit committee from the governance reports published on the website of the Syrian Securities and Markets Authority, as well as data on the dependent variable represented in financial performance through lists and reports The finances of insurance companies listed on the Damascus Securities Exchange and the Syrian Securities and Markets Authority, which are 7 companies, during the period from 2009 to 2017, the data was studied through the Eviews10 program.